Restorative justice: the feasibility of alternative models of justice - Yeager, Matthew G. (Contemporary justice review, 2022)
The issue of overloaded, and backlogged courts is not new. Despite the 2016 Supreme Court of Canada R. v. Jordan ruling which set a “presumptive ceiling” of 18 months for summary and 30 months for indictable cases respectively, the issue can be traced back decades before. In particular, the Supreme Court of Canada has intervened three other times on the issue of unreasonable delays, and the corresponding section of the Canadian Charter of Rights and Freedoms (section 11 (b)). Despite these interventions, the underlying problems which cause court delays remain unaddressed. As a result, new solutions to this persistent problem ought to be considered. This article aims to explore whether or not restorative justice (RJ) is a feasible alternative. In particular, RJ appears to be more efficient, cost less, and result in lower levels of recidivism and higher levels of satisfaction among participants. Despite these benefits, it will be argued that RJ is unlikely to be considered for broader use in Canada due to the political landscape and prevailing beliefs among Canadians regarding punitive punishments. Changes to the Criminal Code might help rectify this dilemma.